Dochody gmin w warunkach transformacji systemu dochodów jednostek samorządu terytorialnego - Sierak, Jacek (Community's Incomes in Conditions of Local Community Unit Income System Transformation, 2006)
Considerable increase in value of community's budget income has been noted between 1991 and 2004. Value of incomes was strictly connected with economy development level and region urbanization degree. In the analyzed period numerous changes in incomes structure have been noted. First positive consequences of new law act concerning local community incomes, which was introduced in 2003, were observed in 2004. It appeared in increase of own incomes value and their participation in general incomes and also in change of local community units subsidize system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 495-506